2021
DOI: 10.1007/s11104-021-05069-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactive regulation of root exudation and rhizosphere denitrification by plant metabolite content and soil properties

Abstract: Aims Root exudates are known to shape microbial activities in the rhizosphere and to be of fundamental importance for plant-soil-microbe-carbon–nitrogen interactions. However, it remains unclear how and to what extent the amount and composition of root exudation affects rhizosphere denitrification. Methods In this study root exudation patterns and rhizosphere denitrification enzyme activity of three different grass species grown on two agricultural soils u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Soil metabolite patterns and quantities depend on plant age, species, and environment (Maurer et al, 2021). In a study of greenhouse pepper cultivation, soil metabolites were found to differ between RS and BS, and the abundance of metabolites was higher in RS than in BS (Song et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Soil metabolite patterns and quantities depend on plant age, species, and environment (Maurer et al, 2021). In a study of greenhouse pepper cultivation, soil metabolites were found to differ between RS and BS, and the abundance of metabolites was higher in RS than in BS (Song et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Table S1). Instead, it is likely that the temporal patterns are directly related to root exudation, which in turn might reflect plant requirements driven by environmental conditions such as water or nutrient availability (Maurer et al, 2021). For example, the sharp decrease in AMF biomass in July, when the biomass of most other free-living microorganisms peaked, suggests altered root exudation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations exist that could explain such observations. These incude legumes' symbiotic N 2 xation, which enhances soil health by supplementing it with nutrients [8,11], root exudations (i.e., sugars, organic, and amino acids and secondary metabolites, such as avonoids, phenolic, and terpenoids) [75], bene cial soil bacterium (e.g., rhizobia, phosphate-solubilizing, and potassium-solubilizing bacteria) that aids in improving soil physio-chemical properties and nutrient availability [69]. For example, legume crop N xation ability could help improve soil-accessible N forms (i.e., N, NH 4 , and NO 3 ) during intercropping [24].…”
Section: Discussionmentioning
confidence: 99%